The Moderating Effect of Time Management on the Relationship between Quality of Work Life and Personal Effectiveness of Junior High School Teachers in Davao Region - IMPAS, RUELAN TEÑAJORA (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
The ultimate aim of this study was to determine the moderating effect of time management on the relationship between quality of work life and personal effectiveness of junior high school teachers in Davao Region. Adapted survey questionnaires were given to a sample of 400 teachers from public junior high schools in the region. Findings revealed that the levels of quality of work life, personal effectiveness and time management are high. Further, findings revealed that quality of work life is significantly related to personal effectiveness. Time management also showed a positive significant relationship to personal effectiveness. To determine the moderating effect of time management, a logistic hierarchical regression was employed in this study. Results revealed that time management has no significant moderating effect on the relationship between quality of work life and personal effectiveness. Teachers who have higher and lower levels of time management demonstrated the same degree of personal effectiveness as influenced by quality of work life. Keywords- education; moderating effect; personal effectiveness; Philippines; quality of work life; time management